TRANSFERSOMAL GEL CONTAINING GREEN TEA (CAMELLIA SINENSIS L. KUNTZE) LEAVES EXTRACT: INCREASING IN VITRO PENETRATION - Anwar, Effionora; Utami, Tahmida Diazputri; Ramadon, Delly (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to increase penetration of EGCG from green tea leaves extract (Camellia sinensis L. Kuntz) through the skin by formulating them into a transfersomal gel. Methods: Transfersomes were prepared by thin-layer hydration method, with different concentration of the extract that equivalent to 1% (F1), 1.5% (F2), and 2% (F3) EGCG. Transfersomes formula with good characteristics would be incorporated into a gel formulation. A gel without transfersomes prepared as a control of comparison. Both of gels were evaluated their physicochemical properties. In vitro penetration test using Franz diffusion cell with the skin of female Sprague-Dawley rats was also performed. Results: The results showed that F1 had the best physicochemical properties. F1 had a spherical shape, Dmean volume at 107.82±0.44 nm, polidispersity index at 0.07±0.01, zeta potential at -40.3±0.10 mV, and entrapment efficiency at 63.16±0.65%. Cumulative amount of EGCG penetrated from transfersomal and non-transfersomal gel were were 1302.63±20.67 μg/cm2 and 414.86±4.40 μg/cm2, resepctively (P<0.05). Flux penetration of transfersomal and non-transfersomal gel were was 57.594±0.91 μg/cm2.h and 36.144±1.22 μg/cm2.h, respectively. Conclusion: It can be concluded that transfersomal gel could increase the in vitro penetration of EGCG from green tea leaves extract compared to non-transfersomal one.